A new Theosbaena (Thermosbaenacea: Halosbaenidae) from Thailand - Rogers, D. Christopher; Sanoamuang, La-Orsri (Zootaxa, 2016)
We present a second species of Theosbaena, which also represents the second species of Thermosbaenacea from mainland Asia. This new species is apparently endemic to a limestone cave in Nakhon Sawan Province in central Thailand. Theosbaena kiatwongchai n. sp. is separated from T. cambodjiana by the form of the gnathopod, the form of the pereopod exopodites, the lack of a pleopod I, and a cleft telson.